The World Book dictionary - World Book, Inc (Chicago World Book, 2009)
"A two-volume dictionary providing the meaning, spelling, and pronunciation of approximately 225,000 important and frequently used words and phrases in the English language. Features include illustrations, illustrative sentences, and a "Guide to Communications" covering punctuation and spelling tips; vocabulary lists by grade level; how to write effectively, and articles on special subjects"--Provided by publisher
v. 1. A-K -- v. 2. L-Z
1
Keywords: English language -- Dictionaries